Trading Jerusalem: Jewish-Arab Encounters in a Middle Eastern Restaurant in Toronto - Roginsky, Dina; Cohen, Rina (Canadian Jewish Studies / Études juives canadiennes, 2018)
This ethnographic study explores everyday encounters between Jewish Israeli immigrants, Palestinian Arab immigrants, and Canadian Jews in Jerusalem Restaurant a Middle Eastern dining establishment in Toronto. The article reveals the waysin which these three subgroups relate to each other economically and culturally in the context of a diasporic food business that bases its appeal on the symbolism of Jerusalem. Through the practices and relationships observed in this restaurant, we suggest that these subgroups create a practical foodway community, while each subgroup associates with the notion of Jerusalem in its own distinctive way.